2015
DOI: 10.4269/ajtmh.14-0694
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Markers of Environmental Enteropathy are Associated with Animal Exposure and Caregiver Hygiene in Bangladesh

Abstract: Abstract. Undernutrition is estimated to be an underlying cause of over half of all deaths in young children globally. There is a growing body of literature suggesting that increased exposure to enteric pathogens is responsible for environmental enteropathy (EE), a disorder associated with impaired growth in children. To determine if household unsanitary environmental conditions were significantly associated with EE and stunting in children, we conducted a cohort of 216 children (≤ 30 months) in rural Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
114
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(130 citation statements)
references
References 46 publications
9
114
2
Order By: Relevance
“…42 The significant associations between unsafe child feces disposal and elevated environmental enteropathy scores and faltering growth is consistent with the growing body of literature demonstrating that unsanitary environmental conditions put children at an increased risk of environmental enteropathy and impaired growth. [5][6][7] In our previous studies among children in the cohort, we have found that poor caregiver hand hygiene, presence of animals in the child's sleeping room, and children mouthing dirt during play behavior were all significantly associated with elevated fecal markers of environmental enteropathy. 6,7 In addition, an earlier study in rural Bangladesh found that children in "contaminated" households defined by water quality, unhygienic handwashing conditions, and unimproved sanitation had lower lactulose:mannitol, a measure of intestinal absorptive capacity, and impaired growth.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…42 The significant associations between unsafe child feces disposal and elevated environmental enteropathy scores and faltering growth is consistent with the growing body of literature demonstrating that unsanitary environmental conditions put children at an increased risk of environmental enteropathy and impaired growth. [5][6][7] In our previous studies among children in the cohort, we have found that poor caregiver hand hygiene, presence of animals in the child's sleeping room, and children mouthing dirt during play behavior were all significantly associated with elevated fecal markers of environmental enteropathy. 6,7 In addition, an earlier study in rural Bangladesh found that children in "contaminated" households defined by water quality, unhygienic handwashing conditions, and unimproved sanitation had lower lactulose:mannitol, a measure of intestinal absorptive capacity, and impaired growth.…”
Section: Discussionmentioning
confidence: 93%
“…[5][6][7] In our previous studies among children in the cohort, we have found that poor caregiver hand hygiene, presence of animals in the child's sleeping room, and children mouthing dirt during play behavior were all significantly associated with elevated fecal markers of environmental enteropathy. 6,7 In addition, an earlier study in rural Bangladesh found that children in "contaminated" households defined by water quality, unhygienic handwashing conditions, and unimproved sanitation had lower lactulose:mannitol, a measure of intestinal absorptive capacity, and impaired growth. 5 Furthermore, these findings build on earlier work demonstrating that unsafe child feces disposal increases the risk of enteric infections and diarrheal disease in pediatric populations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…47,48 Child exposure to animal fecal contamination within the living environment has been reported in studies from Zimbabwe, 13 Peru, 49 and Bangladesh. 12,50 Since information on animal corralling was not collected as part of the 2011 UDHS, we were unable to examine these relationships in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong epidemiological link between EED and poor sanitation, exposure to animal faeces,16 lack of access to soap and water for hand and face washing,27 and consumption of contaminated food and water 28–31. These associations lead to the hypothesis that poor sanitation facilitates a constant exposure to microbes in the small intestine, provoking the chronic inflammatory state and defective integrity of the gut observed in EED.…”
Section: Reducing Eed With Novel Water Sanitation and Hygiene And Numentioning
confidence: 99%